Nucleic acid amplification-based detection methods for SARS-CoV-2 variant detection: research progress review - Xia WU; Xiao ZHANG; Jiayi HAN; Fangxiao XING; Bixiong YE (Zhongguo gonggong weisheng)
The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), continues to spread worldwide. SARS-CoV-2 is prone to mutation, resulting in variants with increased transmissibility, pathogenicity, and immune escape capabilities, posing a significant global threat. To effectively monitor new coronavirus infections, it is necessary to develop diverse detection technologies that are accurate, sensitive, or field-usable for variant identification. This article describes the principles of nucleic acid amplification-based detection techniques for SARS-CoV-2 variants and their applications variant identification and differentiation. It also discusses the advantages and disadvantages of these methods and provides a reference for the accurate identification and efficient detection of SARS-CoV-2 variants.